Wiley Encyclopedia of Composites 2012
DOI: 10.1002/9781118097298.weoc177
|View full text |Cite
|
Sign up to set email alerts
|

Polymer–Clay Nanocomposites

Abstract: The incorporation of nanoparticles in polymer matrices leads to improvements in several physical properties. As a result, nanocomposites have the potential to be used in various fields such as medical devices, automotive and aerospace applications, packaging, and building materials. This article attempts to describe the various types of nanoparticles and polymeric systems that have been involved in nanocomposite production. Particular emphasis is placed on polymer‐clay nanocomposites, their properties, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 277 publications
0
5
0
Order By: Relevance
“…These improvements allow the dispersion of clay platelets to be easier [9]. Even so, the thermal stability of organic cations is crucial to achieve the highest degree of dispersion [10][11][12][13][14][15][16][17][18][19][20]. In other words, these organic ions can be degraded during the mixing process due to effects of temperature and shear forces, resulting in different trends than those expected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These improvements allow the dispersion of clay platelets to be easier [9]. Even so, the thermal stability of organic cations is crucial to achieve the highest degree of dispersion [10][11][12][13][14][15][16][17][18][19][20]. In other words, these organic ions can be degraded during the mixing process due to effects of temperature and shear forces, resulting in different trends than those expected.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the instability of the organically modified clay can also affect the polymer. Matayabas and Turner [20] have found that degradation occurs in the matrix during the preparation of polyethylene terephthalate nanocomposites with modified clay. Yoon et al [14] have observed similar effects in the processing of polycarbonate nanocomposites with clays.…”
Section: Introductionmentioning
confidence: 99%
“…MMT consists of an aluminum ( i.e ., alumina) or magnesium ( i.e ., brucite) octahedral sheet between two silica tetrahedral sheets with sodium or calcium cations. Under proper conditions, organic modification by cationic‐exchange reaction can expand and even delaminate the MMT layers, which in turn results in their intercalation and exfoliation by polymer chains leading to significant improvements in thermal, mechanical and barrier properties . According to Shokrieh et al , the incorporation of an organically modified nanoclay into a polymer concrete made of epoxy resin enhances the compressive strength and fracture toughness by 15 and 8%, respectively, compared with the neat polymer concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, much research work has been carried out on polymer‐layered clay nanocomposites (NCs) obtained by melt blending with a view to improving a range of the key properties of polymeric materials (mainly mechanical, barrier and thermal), and thus expand its commercial applications . More recently, some very promising research work has focused on the addition of highly dispersed organically modified clays to polymer blends with the aim of obtaining new materials that combine the advantages of both polymer and nanoclay modifications .…”
Section: Introductionmentioning
confidence: 99%